2012
DOI: 10.1371/journal.pone.0030625
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche, the Leg Length to Sitting Height Ratio, and Risk of Diabetes in Middle-Aged and Elderly Chinese Men and Women

Abstract: AimsTo evaluate the associations of age at menarche and the leg length-to-sitting-height ratio, markers of adolescent growth, with risk of diabetes in later life.Materials and MethodsInformation from 69,385 women and 55,311 men, aged 40–74 years from the Shanghai Women's Health Study and Shanghai Men's Health Study, were included in the current analyses. Diabetes status was ascertained through biennial in person follow-up. Cox models, with age as the time scale, were used.ResultsThere were 2369 cases of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 40 publications
5
48
0
2
Order By: Relevance
“…In the present study, consistent with previous results [8,9,29], age at menarche was inversely associated with diabetes prevalence even in post-menopausal Korean women. The subjects with age at menarche younger than 13 years old showed high ORs for diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, consistent with previous results [8,9,29], age at menarche was inversely associated with diabetes prevalence even in post-menopausal Korean women. The subjects with age at menarche younger than 13 years old showed high ORs for diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Association between age at menarche and diabetes prevalence in women remains controversial. Several studies proved that early menarche was associated with higher prevalence of diabetes [7][8][9]. However, other studies found no association [10,11].…”
mentioning
confidence: 99%
“…Results from previous studies have shown that a female's AAM affects her health later in life and has been identified as a risk factor for several traits including breast cancer [3,4] , osteoporotic fracture [5] , abnormal lung function [6] and depression [7,8] . Moreover, recent researches mentioned that earlier menarche has also been associated with obesity [9] , type 2 diabetes [10][11][12] as well as increased metabolic syndrome [13,14] , and all these confer an increased risk of cardiovascular disease (CVD). Though several studies have been conducted for Western and Asian women about the relationship between AAM and CVD [15][16][17][18][19][20] , no consensus was achieved and the association of AAM with many cardiovascular (CV) risk factors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Аналогичную взаимосвязь выявили и в двух азиатских наблю-дениях [19,20], в то время как в параллельном ис-следовании у китайских женщин эта связь не была определена [21]. Доказано, что при раннем менар-хе (в 8 лет) повышается уровень инсулиноподоб-ного фактора роста-1, андростендиона, дегидро-эпиандростерон-сульфата, лептина и инсулина натощак, снижается уровень глобулина, связыва-ющего половые стероиды [22], возникает высокий риск метаболического синдрома [23,24,25].…”
Section: ожирениеunclassified